2022
DOI: 10.7458/spp202210025246
|View full text |Cite
|
Sign up to set email alerts
|

Female teachers’ double burden during the pandemic: overcoming challenges and dilemma between career and family

Abstract: The coronavirus disease 2019 (Covid-19) challenged educators, especially female teachers, as they shouldered the double burden of being both teachers and spouses. This study articulates the online teaching experiences of Indonesian women that work as elementary school teachers. Moreover, the study explores strategies implemented by these teachers to overcome this career-family dichotomy. Carried out in Indonesia’s East Java province, this descriptive mixed method study surveyed 347 married female teachers, 212… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…It was a challenging period where they had to balance paid work with unpaid work. These general results align with previously published data showing negative perceptions about women's double burden during this health crisis [35,36]. Additionally, research demonstrated that men also perceived an increase in their domestic workload, however, this extra work is considered a slight increase [37,38] and lower than what women do [39,40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was a challenging period where they had to balance paid work with unpaid work. These general results align with previously published data showing negative perceptions about women's double burden during this health crisis [35,36]. Additionally, research demonstrated that men also perceived an increase in their domestic workload, however, this extra work is considered a slight increase [37,38] and lower than what women do [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…The median women's age was 36 years (IQR: [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Almost half of the women (47.5%) had completed college studies, while 2.8%had an incomplete or complete high school education.…”
Section: General Sample Characteristicsmentioning
confidence: 99%